Oxford reading tree: sounds and letters: book 21 revise and stretch - Hunt, Roderick; Hepplewhite, Debbie Brychta, Alex (Oxford University Press China, 2011)
Phonics Sounds and Letters Books show all the sounds and graphemes from Phase 2 of Letters and Sounds in the context of Oxford Reading Tree scenes, packed with activities for practice and consolidation.